Understanding stakeholders and political networks - Practical Guidance Note - Piron, Laure-Hélène; Mwamba, Wilfred (FCDO and TWP CoP, 2026)
In 2023, the UK Foreign, Commonwealth & Development Office and the Thinking and Working Politically Community of Practice published Understanding political economy analysis and thinking and working politically. This complementary note sets out more detailed guidance on how to undertake a dynamic Stakeholder Analysis and Political Network Mapping, which are core elements of political economy analysis and other forms of politically informed context analysis. This technical note is for use alongside the UK Foreign, Commonwealth & Development Office (FCDO) guide to understanding political economy analysis (PEA) and thinking and working politically and is part of a series of guides on the use of PEA in practice. It sets out more detailed guidance on how to undertake a dynamic stakeholder analysis and political network mapping, both of which can be used to support international cooperation and development partnerships. Stakeholder analysis considers the key actors relevant to an area of work, political network mapping goes further, analysing the relationships between actors. Both tools help practitioners move from a general understanding towards specific, evidence-based decisions. These approaches can contribute to the design and implementation of a strategy, policy dialogue or development programme, and to the management of risks This guide has been produced jointly with the Thinking and Working Politically Community of Practice (TWP CoP). The TWP CoP is a global network of practitioners and researchers in international cooperation committed to helping practitioners understand how change happens and why. The TWP CoP Secretariat has been hosted by the University of Birmingham with support from FCDO.

Thinking and Working Politically: Learning from practice. Overview to Special Issue - McCulloch, Neil; Piron, Laure-Hélène (Development Policy Review, 2019)
Over the last 15 years, a set of ideas now referred to as “thinking and working politically” (TWP) has coalesced into a “second orthodoxy” about how to take context into account when implementing development interventions. This approach stresses the importance of obtaining a better understanding of the local context (“thinking politically”) in order to support local actors to bring about sustainable developmental change (“working politically”). However, the evidence base to justify this new approach remains thin, despite a growing number of programmes which purport to be implementing it. Officials in development agencies struggle with putting it into practice and it is unclear how TWP differs—or not—from similar approaches, such as Problem Driven Iterative Adaptation (PDIA) and Doing Development Differently (DDD). This Special Issue sheds light on what TWP means in practice by examining a set of initiatives undertaken by both development partners and government departments in Nigeria, the Occupied Palestinian Territories, China and India. This overview article outlines, in brief, each of the Special Issue's four papers and then draws out five lessons—for funders and for practitioners—from across all the papers. Our five lessons are: (1) the fundamental importance of undertaking political economy analysis (PEA) to adapt programmes to their contexts; (2) the importance of having a realistic level of ambition for interventions; (3) the need to support local ownership—not just “agreement ownership” (between a donor agency and government) or local “management ownership” of the programme, but critically “driver ownership” by generating trust with the key local actors driving change; (4) the need for a more effective set of tools for measuring results in complex programmes that attempt to achieve improvements in long-run governance; and, (5) that although the political economy of donors is often seen as a barrier to applying TWP, the articles show how much can be done with a TWP approach if the analysis takes into account the political economy of donors as well as that of the local context. We conclude with a set of operational recommendations for donors and implementors, as well as suggestions of avenues for further research.
Keywords: Adaptation; Development programmes; Political economy analysis; Reform space; thinking and working politically

Understanding Political Economy Analysis and Thinking and Working Politically - Whaites, Alan; Piron, Laure-Hélène; Menocal, Alina Rocha; Teskey, Graham (FCDO and TWP CoP, 2023)
This guide is adapted from work by the UK Foreign, Commonwealth and Development Office (FCDO) with inputs from members of the Thinking and Working Politically Community of Practice (TWP CoP). It outlines how to understand and use a set of analytical tools that are collectively known as Political Economy Analysis (PEA). The guide aims to equip practitioners to act in an informed manner, given that development objectives are invariably politically complex, and entail engaging with counterparts’ political incentives and preferences. The guide summarises different types of tools – from very light-touch to more in-depth approaches – and provides advice on how development professionals can decide what is most appropriate in a given context, with illustrations based on the experiences of teams working on these issues. This guide will help development professionals and others to make use of PEA and to apply it to their own specific needs. The first part of the guide offers a general picture of the approach. The second part provides more specific guidance for those who are tasked with deploying a PEA. Contents --> Main audience What is PEA, its role and purpose (Section 2) --> General information for all readers The main elements of PEA (Section 3) Thinking and Working Politically (Section 4) --> Core information for teams planning and using PEA How to ensure quality (Section 5) --> Essential reading for those directly responsible for a PEA Important concepts and terminology (Annex) --> General information for all readers